Research on Influence of Tank Sloshing on Ship Motion Response under Different Wavelengths - Xinsheng Fan; Zhenhong Hu; Xing Zheng (Applied Sciences, 2022)
The motion of the liquid-carrying ship under waves is simultaneously affected by the external wave moment and the sloshing moment of the internal tank, which makes the motion of the ship more complicated. In order to explore the influence of tank sloshing on the ship motion response, the motion of the ship model with tanks at different wavelengths were simulated based on the CFD software. This paper is based on the finite volume method (FVM) to solve the RANS (Reynolds averaged Navier-Stokes) equation for numerical simulation, and the VOF (volume of fluid) method was used to capture the free surface. Using the VOF method, it is necessary to ensure that the mesh at the free surface is sufficiently fine. Based on the above conditions, the pitching motion and rolling motion of the liquid carrier in the head sea condition and the transverse wave condition were simulated, respectively. The results showed that the sloshing of the tank has little influence on the pitching motion but has a greater influence on the rolling motion. When the liquid loading rates were 0, 0.8, 0.9, and 0.98, the pitch angle changes of the ship under different wavelengths were basically the same. However, when the liquid loading rates were 0, 0.4, and 0.8, the roll angle of the ship varied greatly under different wavelengths. By simulating the roll free decay motion of the liquid carrier (the loading rates were 0, 0.2, 0.4, 0.6, 0.8 and 0.98), it was found that the essence of the sloshing effect of the tank is to change the amplitude of the ship’s rolling motion by changing the natural frequency of the ship’s rolling motion. The closer the incident wave frequency is to the natural frequency of the roll of the liquid carrier, the greater the roll amplitude of the ship.